Penyuluhan dan Pemeriksaan Kesehatan (Status Gizi dan Range of Motion Plantar Flexi Pergelangan Kaki) - Indriyani, Indriyani; Badri, Putri Rizki Amalia; Oktariza, Rury Tiara; Ramadhan, Irzan (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2025)
Musculoskeletal Disorders (MSDs) are health problems that are common and can be experienced by anyone, not limited to a specific age. Several studies have shown that there is a relationship between ergonomic knowledge and MSD complaints, one of which is the Range of Motion (ROM) of the ankle plantar flexion. This service activity was carried out for 25 students at SMK Muhammadiyah 3 Palembang in October 2024 offline. The form of service activities is in the form of counseling and health checks, in the form of nutritional status checks, and ROM Plantar Flexion ankle. The results showed that as many as 18 (72%) respondents had normal plantar flexion ROM results, and as many as 7 (28%) respondents had abnormal plantar flexion ROM results. As well as the results of increasing knowledge, seen from the increase in mean values between pretests and posttests. By increasing public knowledge through effective, easy-to- understand, and relevant education, we can increase people's awareness of health, so that they can live a more comfortable and quality life.